2010
DOI: 10.1007/s10115-010-0348-2
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining scalable and accurate classification in large-scale spatio-temporal domains

Abstract: We present an approach for learning models that obtain accurate classification of data objects, collected in large-scale spatio-temporal domains. The model generation is structured in three phases: spatial dimension reduction, spatio-temporal features extraction, and feature selection. Novel techniques for the first two phases are presented, with two alternatives for the middle phase. We explore model generation based on the combinations of techniques from each phase. We apply the introduced methodology to dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…For this reason, a typical approach is to find a method that works satisfactorily for a specific problem setting. New feature selection methods are constantly emerging using different strategies: a) combining several feature selection methods, which could be done by using algorithms from the same approach, such as two filters [28], or coordinating algorithms from two different approaches, usually filters and wrappers [29,30]; b) combining feature selection approaches with other techniques, such as feature extraction [31] or tree ensembles [32]; c) reinterpreting existing algorithms [33], sometimes to adapt them to specific problems [34]; d) creating new methods to deal with still unresolved situations [35,36]; and e) using an ensemble of feature selection techniques to ensure better behavior [37,38].…”
Section: Other Approachesmentioning
confidence: 99%
“…For this reason, a typical approach is to find a method that works satisfactorily for a specific problem setting. New feature selection methods are constantly emerging using different strategies: a) combining several feature selection methods, which could be done by using algorithms from the same approach, such as two filters [28], or coordinating algorithms from two different approaches, usually filters and wrappers [29,30]; b) combining feature selection approaches with other techniques, such as feature extraction [31] or tree ensembles [32]; c) reinterpreting existing algorithms [33], sometimes to adapt them to specific problems [34]; d) creating new methods to deal with still unresolved situations [35,36]; and e) using an ensemble of feature selection techniques to ensure better behavior [37,38].…”
Section: Other Approachesmentioning
confidence: 99%
“…Past research has shown that subset of features could represent the data more efficiently and leads to better understanding (Vainer et al 2011). Datasets with irrelevant and redundant information could lead to a complicated learning process and less accurate results (Tuv et al 2009).…”
Section: Related Work Dengue Outbreak Detectionmentioning
confidence: 99%
“…Zhang et al (2008) apply reliefF and mRMR as a combination of different algorithms from the same approach (filters), whereas El Akadi et al (2011) apply mRMR filter and GA wrapper using filters and wrappers approaches. On the other hand, other works combined feature selection with other processes, such as combining spatial dimension reduction, spatiotemporal features extraction, and feature selection for hurricane severity classification (Vainer et al 2011). Tuv et al (2009 proposed feature selection with ensembles, artificial variables and redundancy elimination.…”
Section: Feature Selectionmentioning
confidence: 99%
“…However, most researchers agree that there is not a so-called "best method" and their efforts are focused on finding a good method for a specific problem set. Therefore, the recent feature selection methods are constantly appearing using different strategies: a) combining several feature selection methods, which could be done by using algorithms from the same approach, such as two filters [130], or coordinating algorithms from two different approaches, usually, filters and wrappers [131,132] b) combining feature selection approaches with other techniques, such as feature extraction [133] or tree ensembles [134]; c) reinterpreting existing algorithms [135], sometimes to adapt them to specific problems [136]; d) creating methods to deal with still unresolved situations [137,138] using an ensemble of feature selection techniques to ensure a better behavior [139,140]).…”
Section: Other Approachesmentioning
confidence: 99%